A Comprehensive Systematic Review of The Relationship between Long-Term Urinary Catheter Use and the Incidence of Recurrent Urinary Tract Infections - Andi Dedi Pradana Putra; Khaeriah B (The International Journal of Medical Science and Health Research, 2026)
Background: Long-term urinary catheterization (≥30 days) is widely used but strongly associated with recurrent urinary tract infections (UTIs). However, the magnitude of risk, comparative safety of catheter types, efficacy of preventive strategies, and trade-offs such as antimicrobial resistance remain debated. Methods: This systematic review synthesized evidence from 80 studies (including randomized controlled trials, cohort studies, meta-analyses, and systematic reviews) examining the relationship between long-term catheter use and recurrent UTIs. Primary outcomes included UTI incidence rates, risk ratios, and the effects of catheter duration, catheter type, coatings, antibiotic prophylaxis, care bundles, irrigation protocols, and non-antibiotic strategies. Results: A dose-dependent relationship was identified, with UTI risk increasing approximately 5% per catheterization day and reaching near-certainty at 30 days (OR 3.03 for long-term indwelling catheters in kidney recipients). Early catheter removal (≤3 weeks) reduced UTI odds by 47–59%. Antimicrobial-coated catheters showed modest benefit (OR 0.80), but noble metal alloy catheters reduced CAUTI by 69% (IRR 0.31). Hydrophilic intermittent catheters significantly lowered UTI risk (OR 0.36). Continuous antibiotic prophylaxis reduced symptomatic UTIs by 48% but increased resistance to nitrofurantoin (24% vs 9%) and trimethoprim (67% vs 33%). Nurse-driven protocols and reminder systems reduced CAUTI by 52–56%, and twice-weekly bladder irrigation was optimal (IRR 0.40). Probiotics showed no significant benefit, while D-mannose and bowel management in spina bifida were promising. Discussion: The evidence confirms a strong duration–risk relationship, supports coated catheters for long-term use, highlights the efficacy–resistance trade-off of antibiotic prophylaxis, and emphasizes institutional protocols as the most consistently effective interventions. Indwelling versus intermittent catheterization shows no clear infection-related superiority when confounders are considered. Conclusion: Early catheter removal remains the most effective strategy. For long-term users, coated catheters, antibiotic prophylaxis (in selected patients), and optimized irrigation (twice weekly) reduce UTI risk. Future research should focus on non-antibiotic strategies and implementation science.